PENDIDIKAN MITIGASI BENCANA DI SD: MENUMBUHKAN KESADARAN DAN KESIAPSIAGAAN SEJAK DINI - Faizin, Imam; Suharini, Erni; Widiyatmoko, Arif (Institut Daarul Qur'an Jakarta, Indonesia, 2025)
Disaster mitigation education in elementary schools plays a crucial role in raising awareness and preparedness among students to face disasters. SD Negeri 2 Bawang, as one of the schools involved in this program, conducted an earthquake disaster mitigation simulation aimed at improving student preparedness. This study aims to analyze the implementation and impact of disaster mitigation activities on students' understanding and preparedness. The research method used is descriptive qualitative with an observational and interview approach involving the school principal, teachers, and students. The results show that the disaster simulation successfully increased student preparedness, as evidenced by their active participation in training and their ability to follow procedures quickly and accurately. The procedures taught, such as taking shelter under desks, evacuating the building in an orderly manner, and following evacuation routes, were executed well. In conclusion, the disaster mitigation program at SD Negeri 2 Bawang is effective in improving student preparedness, but it requires improved facilities and further training to expand the program to other schools.